Value-added taxation in the EC after 1992: Some applied general equilibrium calculations - Hans Fehr; Christoph B. Rosenberg; Wolfgang Wiegard (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1991)
This paper examines the quantitative effects of the transitional system of value-added taxation for intra-EC trade after 1992, as recently adopted by the ECOFIN-Council. First, the administration of the current destination principle and the interim solution are described and a mathematical formalization is provided. A short representation of the empirical general equilibrium model featuring seven EC regions and 14 production sectors follows. Finally, the effects of a switch to the transitional system are examined theoretically and by using policy simulations. When decomposing welfare effects, international tax revenue shifts prove to dominate, while substitution effects have relatively little influence on economic welfare. A generous arrangement with regard to long distance shopping, opening tax arbitrage possibilities to final consumers, favours low tax countries at the cost of their EC partners. – – Dieser Beitrag untersucht die quantitativen Efgekte der jüngst vom ECOFIN-Rat beschlossenen Übergangsregelung für die umsatzsteuerliche Behandlung des Handels in der EG nach 1992. Zunächst werden die Funktionsweise des bisherigen Bestimmungslandprinzips und der neuen Regelung beschrieben und mathematisch formalisiert. Es folgt eine kurze Darstellung des sieben EG-Regionen und 14 Produktionssektoren pro Land umfassenden empirischen allgemeinen Gleichgewichtsmodells. Im letzten Teil wird zunächst theoretisch und dann anhand von Simulationsrechnungen auf die Wirkungen eines Wechsels zum Übergangssystems eingegangen. Bei einer Zerlegung der Wohlfahrtseffekte zeigt sich, dass internationale Steueraufkommensverschiebungen das Ergebnis quantitativ dominieren, während Substitionseffekte kaum Einfluss auf die ökonomische Wohlfahrt haben. Bei einer großzügigen Versandhandelsregelung, die den Endkonsumenten Möglichkeiten der Steuerarbitrage eröffnet, gewinnen Niedrigsteuerlander auf Kosten ihrer EG-Partner.
Keywords: 330